Indexing and searching petabase-scale nucleotide resources - Shiryev, Sergey A.; Agarwala, Richa (Nature methods, 2024)
Searching vast and rapidly growing nucleotide content in resources, such as runs in the Sequence Read Archive and assemblies for whole-genome shotgun sequencing projects in GenBank, is currently impractical for most researchers. Here we present Pebblescout, a tool that navigates such content by providing indexing and search capabilities. Indexing uses dense sampling of the sequences in the resource. Search finds subjects (runs or assemblies) that have short sequence matches to a user query, with well-defined guarantees and ranks them using informativeness of the matches. We illustrate the functionality of Pebblescout by creating eight databases that index over 3.7 petabases. The web service of Pebblescout can be reached at https://pebblescout.ncbi.nlm.nih.gov . We show that for a wide range of query lengths, Pebblescout provides a data-driven way for finding relevant subsets of large nucleotide resources, reducing the effort for downstream analysis substantially. We also show that Pebblescout results compare favorably to MetaGraph and Sourmash. The Pebblescout tool achieves an efficient search for subjects in a large nucleotide database such as runs in Sequence Read Archive data.